Partnership for Peace: The Project and Its Critics (Czech Journal of International Relations, 2024)
Jiří Stepanovsky:born 1925, graduated from the Faculty of Law of Charles University. He taught the history of international relations at VŠPHV, then he was head of the department of developing countries at the ÚMPE. In 1968-1969 he was a visiting professor of political science in Chicago. In the years 1970-1989 he was employed outside his field. In 1990-1991, he worked at the Institute of International Relations. He is the chairman of the Czech Atlantic Commission, a member of the editorial board of the journal International Relations and International Politics.